Improving Outcomes in Patients With Sepsis. (January 2016) - Armen, Scott B.; Freer, Carol V.; Showalter, John W.; Crook, Tonya; Whitener, Cynthia J.; West, Cheri; Terndrup, Thomas E.; Grifasi, Marissa; DeFlitch, Christopher J.; Hollenbeak, Christopher S.
Sepsis mortality may be improved by early recognition and appropriate treatment based on evidence-based guidelines. An intervention was developed that focused on earlier identification of sepsis, early antimicrobial administration, and an educational program that was disseminated throughout all hospital units and services. There were 1331 patients with sepsis during the intervention period and 1401 patients with sepsis during the control period. After controlling for expected mortality, patients in the intervention period had 30% lower odds of dying (odds ratio = 0.70, 95% confidence interval [CI] = 0.57 to 0.84). They also had 1.07 fewer days on average in the intensive care unit (95% CI = −1.98 to −0.16), 2.15 fewer hospital days (95% CI = −3.45 to −0.86), and incurred on average 1949 less in hospital costs, although the effect on costs was not statistically significant. Continued incremental improvement and sustainment is anticipated through organizational oversight, continued education, and initiation of an automated electronic sepsis alert function.